4-Chloro-2-[(E)-(4-nitrophenyl)diazenyl]phenol - Aslanov, Leonid A. (International Union of Crystallography, 2009)
The title compound, C(12)H(8)ClN(3)O(3), in the crystalline state and in solution, exists in the azo form, as predicted by density functional theory (DFT) calculations. The molecule is approximately planar [the dihedral angle between the rings is 1.83 (8)°], with the nitro group slightly twisted [13.4 (2)°] relative to the benzene ring. Translationally related molecules form stacks along [010] with an interplanar distance of 3.400 (2) Å. The hydroxy group forms an intramolecular hydrogen bond with the azo N atom.